Australian Gay and Bisexual Men's Use of Erectile Dysfunction Medications During Recent Sexual Encounters. (29th November 2013) - Prestage, Garrett; Jin, Fengyi; Bavinton, Benjamin; Grulich, Andrew; Brown, Graham; Pitts, Marian; Hurley, Michael
Abstract Aim Use of erectile dysfunction medications (EDMs) is relatively common among gay and bisexual men and has been associated with human immunodeficiency virus sexual risk behavior. We aimed to determine what factors were related to EDM use on occasions when participants engaged in protected anal intercourse (PAIC) and when they engaged in unprotected anal intercourse (UAIC) with casual partners. Methods An online cross‐sectional survey was conducted, resulting in a sample of 1, 376 Australian gay and bisexual men who reported an occasion of anal intercourse with casual male partners in the previous year. Main Outcome Measure The main outcome measure was the use of EDM during most recent occasions of PAIC and UAIC. Results Men were as likely to use EDM on occasions when they were using condoms (11.6%) as they were on occasions when they did not use condoms (13.0%). There was no association between use of EDM and self‐esteem, nor was there an association between sexual risk behavior and self‐esteem. Men who used EDM were more sexually active overall and appeared to often use EDM to enhance and extend their sexual experiences. Conclusions Men did not appear to use EDM specifically for the purposes of risk‐taking and mainly used EDM to enhance sexual pleasure. Mental health issues were not indicated by use of EDM. Prestage G, Jin FY, Bavinton B, Grulich A, Brown G, Pitts M, and Hurley M. Australian gay and bisexual men's use of erectile dysfunction medications during recent sexual encounters. J Sex Med 2014;11:809–819.